Effect of nanoconfinement on the formation, structural transition and magnetic behavior of mesoporous copper ferrite - Najmoddin, Najmeh; Beitollahi, Ali; Muhammed, Mamoun; Ansari, Narges; Devlin, Eamonn; Mohseni, Seyed Majid; Rezaie, Hamidreza; Niarchos, Dimitris; Åkerman, Johan; Toprak, Muhammet S. (Journal of alloys and compounds, 2014)
[Display omitted] •Fabrication of superparamagnetic cubic single phase, ordered mesoporous CuFe2O4.•Reduction of formation temperature of copper ferrite through nanoconfinement.•Suppression of Jahn–Teller effect through nanoconfinement.•Stabilization of cubic high temperature phase of copper ferrite at RT.•Investigation of blocking temperature by different methods. Superparamagnetic, cubic single phase, ordered mesoporous copper ferrite is synthesized through confinement in nanocages of mesoporous silica. The heat generated during the reaction is conserved in the silica template pore channels, which allows the formation of copper ferrite at a relatively low processing temperature. The Jahn–Teller distortion is suppressed due to the effect of nanoconfinement and thus the high temperature phase of cubic copper ferrite is stabilized at room temperature. The particle size obtained from TEM, the crystallite size calculated from XRD and the magnetic domain size estimated from magnetization measurements are all in good agreement, manifesting the significant role of the confinement in the growth and fabrication of crystalline, single magnetic domain, nanoparticles with superparamagnetic behavior at room temperature.